PENGARUH PERCEIVED EASE OF USE, ELECTRONIC TRUST DAN ELECTRONIC SECURITY TERHADAP KEPUTUSAN PENGGUNAAN GOPAY PADA GENERASI Z - Sri Wahyuni Romadhon; Alshaf Pebrianggara; Muhammad Yani (MANAJEMEN DEWANTARA, 2026)
This study aims to examine the extent to which perceived ease of use, electronic trust, and electronic security influence Generation Z's decision to use GoPay. The intense competition among digital wallets in Indonesia makes it crucial to understand the factors that influence users' choice of a particular application. This study employed a quantitative method with a descriptive approach, involving 120 respondents who were active GoPay users. Data were obtained through a Likert-based questionnaire and processed using Partial Least Square Structural Equation Modeling (PLS-SEM). The analysis showed that the three variables ease of use, electronic trust, and electronic security had a positive and significant influence on the decision to use GoPay. The ease of understanding the application's display and information (clear and understandable) was a strong factor that encouraged users to feel comfortable making transactions. Furthermore, user trust in the platform also proved to be crucial, particularly the integrity indicator, which is the most decisive aspect in fostering user confidence. Electronic security was also an important consideration, particularly regarding personal data protection, which is a major concern for the younger generation when choosing a digital wallet service. Overall, the study's findings underscore that ease of use, trust, and security are three key aspects influencing Generation Z's decision to use GoPay. These findings are expected to provide input for e-wallet developers to continue improving aspects of user convenience, service transparency, and transaction security.